Selected topics in environmental and public health - Calvin, Abby (Foster Academics, 2015)
Environmental and public health is a growing concern in today's world. This book exemplifies the global nature of public health. The book's transnational list of authors provides an important view of the future of public health and the increased need to collaborate with public health professionals and the environment experts across the world to address the myriad of public health issues. This book elucidates the ways in which methodological advances are being made to protect and facilitate the sector of public health with respect to the environment.